Pengaruh Kompensasi Dan Kepuasan Kerja Terhadap Kinerja Karyawan Dengan Motivasi Kerja Sebagai Variabel Moderasi Pada PT. Pinus Merah Abadi Cabang Metro - Sugeng; Sri Retnaning Rahayu; Indah Kurnia (Jurnal Manajemen DIVERSIFIKASI, 2024)
Based on the company’s employee salary data,it can be seen that the problem of providing compensation is still minimal with the workload given, the compensation given is still below the UMR. This study aims to determine the effect of compensation on employee perfomance, to determine the effect of job satisfaction on employee performance, to determine work motivation in moderating compensation on employee perfomance, to determine work motivation in moderating job satisfaction on employee perfomance. The population in this study are employees of PT. Pinus Merah Abadi, Metro Branch, with 35 employees collecting data using questionnaires, and analyzing data using Validity Test, Reliability Test, Normality Test, Homogeneity Test, Linearity Test, Multiple Linear Regression Analysis, T Test, F Test, R2 Termination, MRA Test and Test Statistical hypothesis with program (SPSS 24). The results of study indicate that compensation has no effect on employee perfomance, job satisfaction has an effect on employee perfomance, job satisfaction has an effect on employee performance, work motivation cannot moderate the relationship between compensation variables and employee perfomance variables, work motivation cannot moderate the relationship between job satisfaction and employee performance variables.